Hydrogen passivation method of TBC solar cell, preparation method of TBC solar cell and TBC solar cell
By using HDPCVD or ICPCVD technology to passivate hydrogen on TBC solar cells, the Si:H suspension bond layer is formed, which solves the problem of unsatisfactory surface passivation effect and improves the conversion efficiency and passivation speed of the battery.
Patent Information
- Application Number
- CN202411570179.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-18
AI Technical Summary
The existing TBC solar cells have poor surface passivation effect, resulting in photogenerated carriers being recombined before reaching the back PN junction region, reducing the conversion efficiency of the battery.
High-density plasma-enhanced chemical vapor deposition (HDPCVD) or inductively coupled plasma-enhanced chemical vapor deposition (ICPCVD) technology is used to passivate the surface of TBC solar cells to form a passivation layer with Si:H hanging bonds.
By improving the passivation speed and effect, the conversion efficiency of TBC solar cells is significantly improved, and the process temperature is low and the substrate is damaged less, which is suitable for combining with low-temperature screen printing processes.
Smart Images

Figure CN119653890A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of TBC solar cells, and in particular to a TBC solar cell hydrogen passivation method, a TBC solar cell preparation method, and a solar cell obtained by the method. Background Art
[0002] There is no metal grid line on the front of the IBC cell (Interdigitated Back Contact). The emitter, back field and corresponding positive and negative metal electrodes are integrated in a forked-finger shape on the back of the cell. This unique structure avoids the metal grid line electrode from blocking light. Combined with the pyramid structure and anti-reflection layer on both the front and back surfaces, it can maximize the use of incident light and reduce more optical losses compared to other solar cells such as PERC. Therefore, it has received widespread attention in the photovoltaic industry.
[0003] However, IBC cells have high requirements for surface passivation; if the surface passivation effect is not ideal, the photogenerated carriers will be recombined before reaching the PN junction area on the back, which will greatly reduce the cell conversion efficiency. Defects in the crystalline silicon material, including impurities, vacancies, lattice distortion, etc., as well as surface defects such as adsorbed impurities and dangling bonds, will become carrier recombination centers, thereby affecting the minority carrier lifetime of the material. Therefore, surface passivation has become a key means to improve the efficiency of TBC solar cells.
[0004] The passivation process refers to the process of reducing the surface recombination of carriers by inactivating existing defects. Field effect passivation and chemical passivation are the two main passivation methods currently. One way of chemical passivation is to deposit a H-rich dielectric layer, which releases free hydrogen to occupy the vacancies of dangling bonds during the metallization sintering process, thereby achieving a passivation effect. Conventional hydrogen passivation technology uses plasma enhanced chemical vapor deposition to form a H-rich layer. However, the diffusion of hydrogen atoms achieved in this way is relatively limited, and the passivation effect needs to be improved. Summary of the invention
[0005] In order to overcome the above problems, the present disclosure provides a new passivation method for TBC solar cells, which performs hydrogen passivation on the surface of TBC solar cells by high-density plasma enhanced chemical vapor deposition (HDPCVD) or inductively coupled plasma enhanced chemical vapor deposition (ICPCVD). Through the passivation method disclosed in the present disclosure, the passivation speed is fast and the passivation effect is good, thereby improving the conversion efficiency of TBC solar cells.
[0006] According to the passivation method of the TBC solar cell disclosed in the present invention, hydrogen or a mixed gas of hydrogen and argon is used for the hydrogen passivation.
[0007] According to the passivation method disclosed herein, the passivation layer formed by deposition is a layer having Si:H dangling bonds, and the thickness of the SiNx:H layer is 1-200 nm.
[0008] According to the passivation method disclosed in the present invention, when hydrogen is used for passivation, the hydrogen flow rate is 100-2000sccm; the deposition temperature is 50-300°C; the time is 1-20 minutes; the process pressure is 0.2-200mbar, and the RF power density is 0.5-500mW / cm 2 .
[0009] According to the passivation method disclosed herein, when a mixed gas of hydrogen and argon is used for passivation, the hydrogen flow rate is 100-2000sccm; the argon flow rate is 100-2000sccm; the volume ratio of hydrogen / argon in the mixed gas is 0.1-100; the deposition temperature is 50-300°C; the time is 1-20 minutes; the process pressure is 0.2-200mbar, and the RF power density is 0.5-500mW / cm 2 .
[0010] The present disclosure also provides a method for preparing a TBC solar cell, the method comprising the above-mentioned passivation step of passivating the surface of the TBC solar cell by HDPCVD or ICPCVD.
[0011] According to the method for preparing a TBC solar cell disclosed in the present invention, the passivation step is performed after anti-reflection films are plated on the front and back sides of the TBC solar cell.
[0012] The present disclosure also provides a TBC solar cell including a hydrogen passivation layer formed by HDPCVD or ICPCVD.
[0013] According to the passivation method of the TBC solar cell disclosed in the present invention, the passivation treatment temperature is low, the damage to the substrate is small, and it can be matched with a low-temperature screen printing process. According to the preparation method of the TBC solar cell disclosed in the present invention, only one process needs to be added in the battery preparation process, and the process time is short, and the passivation effect is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The present invention is a flow chart of a method for preparing a TBC solar cell according to the present invention.
[0015] Figure 2 is a structural diagram of a TBC solar cell according to the present disclosure. DETAILED DESCRIPTION
[0016] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the technical solution of the present disclosure is described in detail below with reference to the accompanying drawings.
[0017] Example embodiments will be described more fully below with reference to the accompanying drawings, but the example embodiments may be embodied in different forms and should not be construed as limited to the embodiments set forth herein. On the contrary, the purpose of providing these embodiments is to make the present disclosure thorough and complete and to enable those skilled in the art to fully understand the scope of the present disclosure.
[0018] In the absence of conflict, the various embodiments of the present disclosure and the various features therein may be combined with each other.
[0019] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0020] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. As used herein, the singular forms "a", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It will also be understood that when the terms "comprising" and / or "made of" are used in this specification, the presence of the features, wholes, steps, operations, elements and / or components is specified, but the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or groups thereof is not excluded.
[0021] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art. It will also be understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and the present disclosure, and will not be interpreted as having an idealized or overly formal meaning unless explicitly defined as such herein.
[0022] The localized defects on the surface or grain boundary of crystalline silicon TBC solar cells are mainly caused by the following three reasons: 1) Dangling bonds, which are mainly crystal defects caused by broken bonds on the substrate surface. 2) Impurity doping introduced by the process during the device preparation process, which will introduce dead layer (unactivated dopant) defects in the case of high concentration doping, causing lattice distortion. In addition, Auger recombination will be introduced under high concentration doping. 3) Silicon crystals introduce impurities, poor crystals and other defects during the preparation of silicon ingots. The principle of hydrogen passivation is that hydrogen atoms diffuse into the silicon body and surface during the metallization process and interact with dangling bonds to achieve the passivation effect. In order to better passivate, hydrogen atoms must exist in the form of ions. In the process of high-energy particle treatment, H2 forms H plasma under the action of RF generator (radio frequency generator) and ICP generator (inductively coupled plasma generator). Under the action of magnetic field and its own kinetic energy, H reaches the surface of silicon wafer, forms Si-H bonds, reduces Si dangling bond density, reduces silicon wafer surface recombination, and thus improves the minority carrier lifetime of silicon wafer.
[0023] The present invention provides a passivation method for a TBC solar cell, which uses hydrogen or a mixture of hydrogen and argon to hydrogen-passivate the surface of the solar cell by high-density plasma enhanced chemical vapor deposition (HDPCVD) or inductively coupled plasma enhanced chemical vapor deposition (ICPCVD). The passivation method disclosed in the present invention has a fast passivation speed and a good passivation effect, thereby improving the conversion efficiency of the TBC solar cell.
[0024] According to the passivation method disclosed herein, the passivation layer formed by deposition is a layer having Si:H dangling bonds, and the thickness of the SiNx:H layer is 1-200 nm.
[0025] According to the passivation method disclosed in the present invention, when hydrogen is used for passivation, the hydrogen flow rate is 100-2000sccm; the deposition temperature is 50-300°C; the time is 1-20 minutes; the process pressure is 0.2-200mbar, and the RF power density is 0.5-500mW / cm 2 .
[0026] According to the passivation method disclosed herein, when a mixed gas of hydrogen and argon is used for passivation, the hydrogen flow rate is 100-2000sccm; the argon flow rate is 100-2000sccm; the volume ratio of hydrogen / argon in the mixed gas is 0.1-100; the deposition temperature is 50-300°C; the time is 1-20 minutes; the process pressure is 0.2-200mbar, and the RF power density is 0.5-500mW / cm 2 .
[0027] The present disclosure also provides a method for preparing a TBC solar cell, the method comprising the above-mentioned passivation step of passivating the surface of the TBC solar cell by HDPCVD or ICPCVD.
[0028] According to the method for preparing a TBC solar cell disclosed in the present invention, the passivation step is performed after anti-reflection films are plated on the front and back sides of the TBC solar cell.
[0029] According to one embodiment of the present disclosure, referring to Figure 1 The method for preparing the TBC solar cell comprises the following steps:
[0030] S1-clean and texturize the silicon wafer;
[0031] S2-Alkali polishing of the front and back sides of the silicon wafer;
[0032] S3-depositing amorphous silicon on the back side of the silicon wafer;
[0033] S4-boron diffusion and annealing of amorphous silicon;
[0034] S5-Open the film on the back of the silicon wafer to remove the surface oxide layer;
[0035] S6-Alkali polishing removes the PN junction in the film area;
[0036] S7-depositing amorphous silicon on the back side of the silicon wafer;
[0037] S8-diffusion of phosphorus and annealing of amorphous silicon;
[0038] S9-Open the film on the back of the silicon wafer to remove the surface oxide layer;
[0039] S10-Alkali polishing removes the PN junction in the film area;
[0040] S11-anti-reflection coating is applied to the front and back of the silicon wafer;
[0041] S12-Hydrogen passivation of the front and / or back side of the silicon wafer by HDPCVD or ICPCVD; and
[0042] S13-screen printing and sintering to obtain battery cells.
[0043] According to another embodiment of the present disclosure, the method for preparing the TBC solar cell comprises the following steps:
[0044] S1-Cleaning and texturing of silicon wafers.
[0045] Use alkaline solution to texture the double sides of silicon wafers to remove the damaged layer on the surface of silicon wafers and form a surface light trapping structure;
[0046] S2-Alkali polishing of the front and back sides of the silicon wafer.
[0047] The front and back sides of the silicon wafer are alkaline polished at 70-90° C. using a KOH solution having a concentration of 15-30 wt %.
[0048] S3-Deposit amorphous silicon on the back side of the silicon wafer.
[0049] Low pressure chemical vapor deposition (LPCVD) is used to deposit a tunneling oxide layer and an amorphous silicon thin film layer on the back of the battery. The thickness of the tunneling oxide layer is less than 2nm, and the amorphous silicon thin film layer is in-situ doped and has a thickness of 30 to 200nm.
[0050] S4-Boron diffusion and annealing of amorphous silicon.
[0051] The amorphous silicon film is doped with boron and annealed in a tubular high-temperature annealing furnace to transform the amorphous silicon into a polycrystalline silicon layer. The process temperature is 700-1000℃ and the process time is 1-2h. The doping concentration after activation is 1E18-1E21cm -3 .
[0052] S5-Open the film on the back of the silicon wafer to remove the surface oxide layer.
[0053] The surface mask layer of the P region and the insulating region is removed by laser etching, the laser power is 300-800W, and the laser spot size is 50μm x 50μm to 500μm x 500μm.
[0054] S6-Alkali polishing removes the PN junction in the film area.
[0055] Use 15-20wt% KOH to clean and remove the polysilicon film in the film opening area;
[0056] S7-Deposit amorphous silicon on the back side of the silicon wafer.
[0057] Low pressure chemical vapor deposition (LPCVD) is used to deposit a tunneling oxide layer and an amorphous silicon thin film layer on the back of the battery. The thickness of the tunneling oxide layer is less than 2nm, and the amorphous silicon thin film layer is in-situ doped and has a thickness of 30 to 200nm.
[0058] S8-Phosphorus diffusion and annealing of amorphous silicon.
[0059] The amorphous silicon film is doped with boron and annealed in a tubular high-temperature annealing furnace to transform the amorphous silicon into a polycrystalline silicon layer. The process temperature is 700-1000℃ and the process time is 1-2h. The doping concentration after activation is 1E18-1E21cm -3 .
[0060] S9-Open the film on the back of the silicon wafer to remove the surface oxide layer.
[0061] The surface mask layer of the N region and the insulating region is removed by laser etching, the laser power is 300-800W, and the laser spot size is 50μm x 50μm to 500μm x 500μm.
[0062] S10-Alkali polishing removes the PN junction in the film area.
[0063] Use 15-20wt% KOH to clean and remove the polysilicon film in the film opening area;
[0064] S11-Anti-reflection coating is applied to the front and back sides of the silicon wafer.
[0065] Plate-type or tube-type PECVD is used to deposit an anti-reflection film on the front and back of the silicon wafer. The anti-reflection film can be a single-layer film or a multi-layer film formed by SiOx, AlOx, SiNxOy, SiNx or MgFx. The thickness of the anti-reflection film is 50-150nm and the refractive index is 1.9-2.5.
[0066] S12-Hydrogen passivation of the front and / or back side of the silicon wafer by HDPCVD or ICPCVD.
[0067] The hydrogen flow rate is 0-2000sccm; the deposition temperature is 50-300℃; the time is 1-20 minutes; the process pressure is 0.2-200mbar, and the RF power density is 0.5-500mW / cm 2 .
[0068] The hydrogen flow rate is 0-2000sccm; the argon flow rate is 0-2000sccm; the volume ratio of hydrogen / argon in the mixed gas is 0.1-100; the deposition temperature is 50-300℃; the time is 1-20 minutes; the process pressure is 0.2-200mbar, and the RF power density is 0.5-500mW / cm 2 .
[0069] S13-Metallization to make battery cells.
[0070] The anti-reflection film on the back of the silicon wafer is partially removed by laser, and then screen printing and sintering are performed to obtain the battery cell.
[0071] The present disclosure also provides a TBC solar cell including a hydrogen passivation layer formed by HDPCVD or ICPCVD.
[0072] According to one embodiment of the present disclosure, referring to Figure 2 , the TBC solar cell comprises the following structure:
[0073] 1: Silicon wafer 2: n + Polysilicon film 3: p + Polysilicon film 4: Anti-reflection film 1
[0074] 5: Anti-reflection film 2 6: Silicon oxide film 7: N-region metal electrode 8: P-region metal electrode
[0075] In order to enable those skilled in the art to more clearly understand the technical solutions provided by the embodiments of the present disclosure, the technical solutions provided by the embodiments of the present disclosure are described in detail below through specific embodiments:
[0076] Example 1
[0077] The silicon wafer is double-sided textured using an alkaline solution to remove the surface damage layer of the silicon wafer and form a surface light trapping structure; and the front and back sides of the silicon wafer are alkaline polished using a 15wt% KOH alkaline solution at 70°C.
[0078] LPCVD was used to deposit a 1nm thick tunnel oxide layer and an 80nm thick amorphous silicon film layer on the back of the battery. A tubular high-temperature annealing furnace was used to dope the amorphous silicon film with boron and anneal to activate the amorphous silicon layer, transforming the amorphous silicon into a polycrystalline silicon layer. The process temperature was 700℃ and the process time was 2h. The doping concentration after activation was 1E18cm -3 .
[0079] The surface mask layer of the P region and the insulating region was removed by laser etching, the laser power was 300W, and the laser spot size was 50μm x 50μm. 15wt% KOH was used for cleaning to remove the polysilicon film in the film opening area.
[0080] LPCVD was used to deposit a 1nm thick tunnel oxide layer and a 30nm thick amorphous silicon film layer on the back of the battery. A tubular high-temperature annealing furnace was used to dope the amorphous silicon film with boron and anneal to activate the amorphous silicon layer, transforming the amorphous silicon into a polycrystalline silicon layer. The process temperature was 700℃ and the process time was 1h. The doping concentration after activation was 1E18cm -3 .
[0081] The surface mask layer of the N region and the insulating region was removed by laser etching, with a laser power of 300 W and a laser spot size of 50 μm x 50 μm. 15 wt% KOH was used for cleaning to remove the polysilicon film in the film-opening area.
[0082] A silicon nitride film with a thickness of 80 nm and a refractive index of 2.0 was deposited on the front and back sides of the silicon wafer using tubular PECVD.
[0083] The hydrogen flow rate was 1000 sccm, the deposition temperature was 50°C, the deposition time was 3 minutes, the process pressure was 5 mbar, and the RF power density was 200 mW / cm 2 .
[0084] The anti-reflection film on the back of the silicon wafer is partially removed by laser, and then screen printing and sintering are performed to produce TBC solar cells.
[0085] Example 2
[0086] The silicon wafer is double-sided textured using an alkaline solution to remove the surface damage layer of the silicon wafer and form a surface light trapping structure; and the front and back sides of the silicon wafer are alkaline polished using a 20wt% KOH alkaline solution at 90°C.
[0087] A tunnel oxide layer with a thickness of 1.8 nm and an amorphous silicon thin film layer with a thickness of 120 nm were deposited on the back side of the cell using LPCVD.
[0088] The amorphous silicon film was doped with boron and activated by annealing in a tubular high-temperature annealing furnace to transform the amorphous silicon into a polycrystalline silicon layer. The process temperature was 1000°C and the process time was 1h. The doping concentration after activation was 1E21cm -3 .
[0089] The surface mask layer of the P region and the insulating region was removed by laser etching, the laser power was 800W, and the laser spot size was 500μm x 500μm. 20wt% KOH was used for cleaning to remove the polysilicon film in the film opening area.
[0090] A 1.5 nm thick tunnel oxide layer and a 180 nm thick amorphous silicon thin film layer are deposited on the back side of the cell using LPCVD.
[0091] The amorphous silicon film was doped with boron and activated by annealing in a tubular high-temperature annealing furnace to transform the amorphous silicon into a polycrystalline silicon layer. The process temperature was 1000°C and the process time was 1h. The doping concentration after activation was 1E21cm -3 .
[0092] The surface mask layer of the N region and the insulating region was removed by laser etching, with a laser power of 500 W and a laser spot size of 50 μm x 50 μm. 20 wt% KOH was used for cleaning to remove the polysilicon film in the film opening area.
[0093] Plate or tube PECVD is used to deposit a silicon oxynitride film with a thickness of 80 nm on the front and back sides of the silicon wafer, and the refractive index of the film is 2.3.
[0094] The hydrogen flow rate was 1500sccm; the deposition temperature was 100°C; the deposition time was 5 minutes; the process pressure was 10mbar, and the RF power density was 500mW / cm 2 .
[0095] The anti-reflection film on the back of the silicon wafer is partially removed by laser, and then screen printing and sintering are performed to produce TBC solar cells.
[0096] Example 3
[0097] The silicon wafer is double-sided textured using an alkaline solution to remove the surface damage layer of the silicon wafer and form a surface light trapping structure; and the front and back sides of the silicon wafer are alkaline polished using a 15wt% KOH alkaline solution at 80°C.
[0098] A tunnel oxide layer with a thickness of 1.6 nm and an amorphous silicon thin film layer with a thickness of 100 nm were deposited on the back side of the cell using LPCVD.
[0099] The amorphous silicon film was doped with boron and activated by annealing in a tubular high-temperature annealing furnace to transform the amorphous silicon into a polycrystalline silicon layer. The process temperature was 800°C and the process time was 1.5 hours. The doping concentration after activation was 1E20cm -3 .
[0100] The surface mask layer of the P region and the insulating region was removed by laser etching, the laser power was 500W, and the laser spot size was 100μm x 100μm. 18wt% KOH was used for cleaning to remove the polysilicon film in the film opening area.
[0101] A 1.3 nm thick tunnel oxide layer and a 150 nm thick amorphous silicon thin film layer are deposited on the back side of the cell using LPCVD.
[0102] The amorphous silicon film was doped with boron and activated by annealing in a tubular high-temperature annealing furnace to transform the amorphous silicon into a polycrystalline silicon layer. The process temperature was 800°C and the process time was 1.5 hours. The doping concentration after activation was 1E20cm -3 .
[0103] The surface mask layer of the N region and the insulating region was removed by laser etching, with a laser power of 500 W and a laser spot size of 100 μm x 100 μm. The polysilicon film in the film-opening region was removed by cleaning with 20 wt% KOH.
[0104] A silicon oxide film with a thickness of 100 nm and a refractive index of 2.0 is deposited on the front and back sides of the silicon wafer using plate or tube PECVD.
[0105] The hydrogen flow rate was 1200sccm; the deposition temperature was 200℃; the deposition time was 8 minutes; the process pressure was 10mbar, and the RF power density was 200mW / cm 2 .
[0106] The anti-reflection film on the back of the silicon wafer is partially removed by laser, and then screen printing and sintering are performed to produce TBC solar cells.
[0107] Example 4
[0108] The silicon wafer is double-sided textured using an alkaline solution to remove the surface damage layer of the silicon wafer and form a surface light trapping structure; and the front and back sides of the silicon wafer are alkaline polished using a 20wt% KOH alkaline solution at 80°C.
[0109] A tunnel oxide layer with a thickness of 1.5 nm and an amorphous silicon thin film layer with a thickness of 120 nm were deposited on the back side of the cell using LPCVD.
[0110] The amorphous silicon film was doped with boron and activated by annealing in a tubular high-temperature annealing furnace to transform the amorphous silicon into a polycrystalline silicon layer. The process temperature was 800°C and the process time was 1.5 hours. The doping concentration after activation was 1E20cm -3 .
[0111] The surface mask layer of the P region and the insulating region was removed by laser etching, the laser power was 200W, and the laser spot size was 150μm x 150μm. 18wt% KOH was used for cleaning to remove the polysilicon film in the film opening area.
[0112] A 1.3 nm thick tunnel oxide layer and a 150 nm thick amorphous silicon thin film layer are deposited on the back side of the cell using LPCVD.
[0113] The amorphous silicon film was doped with boron and activated by annealing in a tubular high-temperature annealing furnace to transform the amorphous silicon into a polycrystalline silicon layer. The process temperature was 800°C and the process time was 1.5 hours. The doping concentration after activation was 1E20cm -3 .
[0114] The surface mask layer of the N region and the insulating region was removed by laser etching, the laser power was 200W, and the laser spot size was 150μm x 150μm. 18wt% KOH was used for cleaning to remove the polysilicon film in the film opening area.
[0115] A silicon nitride film with a thickness of 100 nm and a refractive index of 1.9 is deposited on the front and back sides of the silicon wafer using plate or tube PECVD.
[0116] The hydrogen flow rate was 1500sccm; the deposition temperature was 200℃; the deposition time was 10 minutes; the process pressure was 15mbar, and the RF power density was 300mW / cm 2 .
[0117] The anti-reflection film on the back of the silicon wafer is partially removed by laser, and then screen printing and sintering are performed to produce TBC solar cells.
[0118] Example 5
[0119] The silicon wafer is double-sided textured using an alkaline solution to remove the surface damage layer of the silicon wafer and form a surface light trapping structure; and the front and back sides of the silicon wafer are alkaline polished using a 15wt% KOH alkaline solution at 70°C.
[0120] A tunnel oxide layer with a thickness of 1.8 nm and an amorphous silicon thin film layer with a thickness of 150 nm were deposited on the back side of the cell using LPCVD.
[0121] The amorphous silicon film was doped with boron and activated by annealing in a tubular high-temperature annealing furnace to transform the amorphous silicon into a polycrystalline silicon layer. The process temperature was 900°C and the process time was 1.5 hours. The doping concentration after activation was 1E21cm -3 .
[0122] The surface mask layer of the P region and the insulating region was removed by laser etching, the laser power was 200W, and the laser spot size was 200μm x 200μm. 15wt% KOH was used for cleaning to remove the polysilicon film in the film opening area.
[0123] A 1.5 nm thick tunnel oxide layer and a 180 nm thick amorphous silicon thin film layer are deposited on the back side of the cell using LPCVD.
[0124] The amorphous silicon film was doped with boron and activated by annealing in a tubular high-temperature annealing furnace to transform the amorphous silicon into a polycrystalline silicon layer. The process temperature was 900°C and the process time was 1.5 hours. The doping concentration after activation was 1E20cm -3 .
[0125] The surface mask layer of the N region and the insulating region was removed by laser etching, the laser power was 200W, and the laser spot size was 200μm x 200μm. 15wt% KOH was used for cleaning to remove the polysilicon film in the film opening area.
[0126] A silicon nitride film with a thickness of 100 nm and a refractive index of 2.1 is deposited on the front and back sides of the silicon wafer using plate or tube PECVD.
[0127] The hydrogen flow rate was 2000sccm; the deposition temperature was 250°C; the deposition time was 15 minutes; the process pressure was 12mbar, and the RF power density was 350mW / cm 2 .
[0128] The anti-reflection film on the back of the silicon wafer is partially removed by laser, and then screen printing and sintering are performed to produce TBC solar cells.
[0129] Comparative Example 1
[0130] The silicon wafer is double-sided textured using an alkaline solution to remove the surface damage layer of the silicon wafer and form a surface light trapping structure; and the front and back sides of the silicon wafer are alkaline polished using a 15wt% KOH alkaline solution at 70°C.
[0131] LPCVD was used to deposit a 1nm thick tunnel oxide layer and an 80nm thick amorphous silicon film layer on the back of the battery. A tubular high-temperature annealing furnace was used to dope the amorphous silicon film with boron and anneal to activate the amorphous silicon layer, transforming the amorphous silicon into a polycrystalline silicon layer. The process temperature was 700℃ and the process time was 2h. The doping concentration after activation was 1E18cm-3 .
[0132] The surface mask layer of the P region and the insulating region was removed by laser etching, the laser power was 300W, and the laser spot size was 50μm x 50μm. 15wt% KOH was used for cleaning to remove the polysilicon film in the film opening area.
[0133] LPCVD was used to deposit a 1nm thick tunnel oxide layer and a 30nm thick amorphous silicon film layer on the back of the battery. A tubular high-temperature annealing furnace was used to dope the amorphous silicon film with boron and anneal to activate the amorphous silicon layer, transforming the amorphous silicon into a polycrystalline silicon layer. The process temperature was 700℃ and the process time was 1h. The doping concentration after activation was 1E18cm -3 .
[0134] The surface mask layer of the N region and the insulating region was removed by laser etching, with a laser power of 300 W and a laser spot size of 50 μm x 50 μm. 15 wt% KOH was used for cleaning to remove the polysilicon film in the film-opening area.
[0135] A silicon nitride film with a thickness of 80 nm and a refractive index of 2.0 was deposited on the front and back sides of the silicon wafer using tubular PECVD.
[0136] The hydrogen flow rate was 1000 sccm, the deposition temperature was 50°C, the deposition time was 3 minutes, the process pressure was 5 mbar, and the RF power density was 200 mW / cm 2 .
[0137] The anti-reflection film on the back of the silicon wafer is partially removed by laser, and then screen printing and sintering are performed to produce TBC solar cells.
[0138] The batteries prepared in the embodiments and comparative examples were subjected to performance tests, and the following Table 1 shows a comparison of the performance of each battery.
[0139] Table 1: Comparison of electrical performance of TBC solar cells using the embodiments of the present disclosure and the comparative examples
[0140]
[0141] It can be observed from the data in Table 1 that the TBC solar cell prepared by this method has obvious advantages in energy conversion efficiency and can significantly improve efficiency and reduce costs.
[0142] Example embodiments have been disclosed herein, and although specific terms are employed, they are used and should be interpreted only in a general illustrative sense and not for limiting purposes. In some instances, it will be apparent to those skilled in the art that, unless otherwise expressly noted, features, characteristics, and / or elements described in conjunction with a particular embodiment may be used alone or in combination with features, characteristics, and / or elements described in conjunction with other embodiments. Therefore, those skilled in the art will appreciate that various changes in form and detail may be made without departing from the scope of the present disclosure as set forth in the appended claims.
Claims
1. A passivation method for a TBC solar cell, comprising: The surface of the solar cell is hydrogen passivated by high density plasma enhanced chemical vapor deposition (HDPCVD) or inductively coupled plasma enhanced chemical vapor deposition (ICPCVD).
2. The passivation method of a TBC solar cell according to claim 1, wherein: The hydrogen passivation is performed using hydrogen or a mixed gas of hydrogen and argon.
3. The passivation method of a TBC solar cell according to claim 1, wherein: The passivation layer formed by deposition is a layer having Si:H dangling bonds.
4. The passivation method of a TBC solar cell according to claim 3, wherein: The thickness of the passivation layer is 1-200 nm.
5. The passivation method of a TBC solar cell according to claim 2, wherein: When hydrogen is used for passivation, the hydrogen flow rate is 100-2000sccm; the deposition temperature is 50-300℃; the time is 1-20 minutes; the process pressure is 0.2-200mbar, and the RF power density is 0.5-500mW / cm 2 .
6. The passivation method of a TBC solar cell according to claim 2, wherein: When a mixture of hydrogen and argon is used for passivation, the hydrogen flow rate is 100-2000sccm; the argon flow rate is 100-2000sccm; the volume ratio of hydrogen / argon in the mixed gas is 0.1-100; the deposition temperature is 50-300°C; the time is 1-20 minutes; the process pressure is 0.2-200mbar, and the RF power density is 0.5-500mW / cm 2 .
7. A method for preparing a TBC solar cell, wherein: The method comprises the passivation step of passivating the surface of the TBC solar cell by HDPCVD or ICPCVD as claimed in any one of claims 1 to 6.
8. The method for preparing a TBC solar cell according to claim 7, wherein the passivation step is performed after anti-reflection films are plated on the front and back sides of the solar cell.
9. A TBC solar cell comprising a hydrogen passivation layer formed by the passivation method according to any one of claims 1 to 6.
10. A TBC solar cell obtained by the preparation method according to claim 7.